Perkembangan Islam pada Masa Kerajaan Turki Usmani - Salmah Intan (Jurnal Adabiyah: Humanities and Islamic Studies, 2009)
After the fall of Abbasiyah dynasty, the Islamic political power was gradually left behind. Several colonized territories looked for their own independence in the form of small monarchies. This condition, of course. exacerbated the Islamic political power. This situation was getting better and better after the appearance of the three big monarchies, which were the Usmani monarchy in Turkey, the Mongol in India, the Safawi monarchy in Persia. Of the three monarchies, the Usmani was firstly established and the biggest and existed the longest. The Usmani monarchy had been able to raise the dignity of Islam for several centuries. Severul progression were achieved at that time, including the territory expansion to Europe, Middle East, Egypt, North Africa; and the advancement in scientific and cultural and religious sectors.